Hubungan Pengetahuan Perawat Terhadap Informent Consent di RS Anna Medika - Sahrudi Sahrudi; Muhammad Safrudin (Universitas Malahayati Lampung, 2024)
ABSTRACT Humans are social creatures, namely creatures that need interaction with other humans. The interaction between humans is not only communication, but also involves all aspects of life, including the legal aspect. Individual legal relations between humans are classified as civil law. Civil law relations cover many fields, one of which is in the contractual relationship which is basically created by humans to reinforce the relationship between (their) parties. Objective of the study to determine the level of knowledge about Informed Consent by nurses who carry out nursing care actions for patients at Anna Medika Hospital. The design of this research is a quantitative descriptive research, which is a method that aims to create an objective description or description of a situation using numbers, starting from data collection, interpretation of the data as well as the appearance and results. From a p-value of 0.173, it is known that the p-value is 0.05, which means that Ho is rejected, which means that there is no relationship between the level of knowledge of nurses and the knowledge of informed consent. There is no relationship between knowledge and the relationship between the level of knowledge of nurses and informed consent. Keywords: Informed Consent, Knowledge ABSTRAK Manusia merupakan makhluk sosial, yaitu makhluk yang membutuhkan interaksi dengan manusia lainnya. Interaksi antara manusia tersebut tidak hanya komunikasi saja, tetapi juga menyangkut seluruh aspek kehidupan, tidak terkecuali aspek hukum. Hubungan hukum secara perorangan antar manusia tergolong dalam hukum perdata. Hubungan hukum perdata mencangkup banyak bidang, salah satunya dalam hubungan perjanjian yang pada dasarnya diciptakan manusia untuk mempertegas hubungan antara pihak(mereka). Tujuan iiPenelitian iimengetahui tingkat pengetahuan tentang Informed Consent oleh tenaga perawat yang melakukan tindakan asuhan keperawatan bagi pasien di Rumah Sakit Anna Medika. Desain penelitian ini merupakan penelitian deskriptif kuantitatif adalah suatu modtode yang bertujuan untuk membuat gambaran atatu deskriptif tenang suatu keadaan secara objektif yang menggunakan angka, mulai dari pengumpulan data, penafsiran terhadap data tersebut serta penampilan dan hasilnya. Dari nilai p-Value 0,173 diketaui p-Value 0,05 yang berarti Ho di tolak yang berarti tidak ada hubungan antara tingkat pengetahuan perawat dengan pengetahuan Informed Consent. Tidak ada hubungan antara pengetahuan dengan hubungan tingkat pengetahuan perawat terhadap Informed Consent. Kata Kunci: Informent Consent, Pengetahuan